Normative Analysis of Islamic Business Feasibility Within Legal and Compliance Frameworks - Muhammad Romi (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2026)
This study examines business feasibility from an Islamic perspective by integrating legal aspects and sharia compliance into a unified framework for ethical and sustainable business assessment. Using a qualitative-normative approach with library research and content analysis, it analyzes regulations, fatwas, and academic literature on sharia business feasibility. The findings indicate that business feasibility in Islam extends beyond financial profitability to include legal validity, moral integrity, and compliance with Islamic principles. Business sustainability requires dual compliance with both national regulations and Islamic law. The integration of legal frameworks, including Law No. 21/2008 on Islamic Banking and Law No. 33/2014 on Halal Product Assurance, together with Sharia Supervisory Board (DPS) oversight and internal sharia audits, enhances legal certainty, sharia compliance, and public trust. The study concludes that Islamic business feasibility represents a holistic model balancing economic, legal, and ethical dimensions. It contributes to Islamic business law literature and provides practical guidance for regulators, Islamic financial institutions, and entrepreneurs in implementing maqasid al-shariah-based business evaluation.